IMPACT OF NATIONAL TEACHERS' STANDARDS ON QUALITY AND EFFECTIVE EDUCATION DELIVERY - Dassah, Damanko; Yelletuo, Peter (African Journal of Education and Practice, 2022)
Purpose: The study focused on the impact of the National Teachers' Standards on quality and effective education delivery. Methodology: The study adopted a mixed methods approach. In all, 20 tutors and 500 students were selected from 10 Colleges of Education in the Northern part of Ghana using purposive and quota sampling procedures. Data were collected using questionnaire and semi-structured interview guide. Quantitative data were analysed using mean and standard deviation while the qualitative data were analysed using thematic analysis. Findings: The results showed that the student-teachers explained concepts clearly using examples familiar to learners, employed a variety of instructional strategies that encourages learner participation and critical thinking and paid attention to all learners, especially girls and students with Special Educational Needs, created a safe, encouraging learning environment and used appropriate disciplinary methods in the classroom. From the results, it was concluded that that the student-teachers were positively impacted by the National Teachers' Standards in their teaching practices. Unique Contributions to Theory, Practice and Policy: Tutors in Colleges of Education increase their training of student-teachers in terms of keeping of records about learners since this found to be an area that needed improvement. Ghana Tertiary Education Commission together with the National Teachers' Council should encourage and ensure that Colleges of Education are implementing the National Teachers' Standards effectively to better prepare student-teachers. Future researchers can adopt the Reform Theory of Action as used in the current study and use the findings of the current study as support for the theory.